An exploratory study of the implementation of Integrity And Anti-Corruption Course (KIAR) in Malaysian Higher Education - Mohd Fariz, Norfazella; Mohammed, Nor Farizal; Lokman, Norziana; Abu Bakar, Norsuhaily; Mohamed, Norazida (UiTM Cawangan Johor, 2025)
In an earnest bid to combat corruption, Malaysia has developed a mitigation plan to enroll youth in national corrective workshops featuring a compulsory course on integrity and anti-corruption for all students entering Malaysian universities beginning in October 2023. This paper, therefore, aims to explore the effectiveness of the Integrity and Anti-Corruption (KIAR) compulsory course in all Malaysian universities. Due to the nature of the new implementation, this study utilizes a qualitative approach by interviewing faculty academics involved in developing and delivering the course, university management personnel, and an officer from the Malaysian Anti-Corruption Commission (MACC). In addition, a content analysis of relevant documents is conducted to gain further insights into the course. Despite initial resistance from faculty academics, KIAR has been successfully implemented as a mandatory course through collaboration between the Ministry of Higher Education and the MACC. Each university is granted autonomy in managing the course to fall under the ambit of formal education, while at the same time allowing the integration of elements of informal and nonformal education. The course is classified as General Studies, with the choice of 1 to 3 credit hours for universities to conduct. As the course is newly introduced in the Malaysian environment, the findings provide valuable knowledge on a new approach to fighting corruption. Therefore, this study offers insights into curriculum development and pedagogical approaches. Additionally, it extends social cognitive and constructivist theories in the area of anti-corruption.